Selection of material model of chosen photocurable resin for application in finite element analyses - Miedzińska, Danuta (Technical Sciences, 2021)
In the paper, a literature study of a modelling methods of a photocurable materials developed by additive techniques is presented. The main aim was to assess which material model is appropriate for such kinds of matter. The Finite Element Method and the LS Dyna software was assumed as a possible environment for the investigations. The material models that can be apply for photopolymers analysing were described as well as examples of such materials. The conclusions is that the material model selection must be based on the observation of the material behaviour and the possible loading conditions (e.g. strain rate).